Evaluasi Lembaga Perlindungan Perempuan Mandiri Dalam Pembangunan Pemberdayaan di Kecamatan Sumbawa Kabupaten Banyuasin - Muhammad Febrianza; Nopriawan Mahriadi; Marleni Marleni; Fathia A Fathia A; Ong Berlian (Universitas Muara Bungo, 2025)
The aim of this study is to evaluate women's protection institutions in terms of empowerment, so that services and innovations for resolving issues are in line with the ongoing situation. The focus of the research is the evaluation of the institution. The research method uses a qualitative approach, with data collection through interviews, observations and documentation in the field. The theory used in this study is the CIPP (Context, Input, Process, Product) evaluation model by Stufflebeam. The results of the study show that there are indicators in the independent women's protection institution that are not optimal, so there is a need for additional resources. Context evaluation revealed that there are limitations in terms of needs and the scope of the area, which must be expanded as soon as possible. Input evaluation revealed a shortage of human resources, funding and supporting facilities, which need to be increased for optimal performance. Process evaluation found that the programme was already being implemented well, in line with the previously set objectives, but adjustments were needed in light of the ongoing development of science and technology. In the product evaluation, the implementation of existing programmes and the addition of new programmes in line with the evolving issues facing women must be carried out on a continuous basis. There is a need for programmes and activities to be publicised so that the community is willing to open up and report any problems they experience. Empowering institutions like this can serve as examples or pioneers for other regions, with the aim of achieving independence, welfare and solving women's issues.